Analysis Of The Open Selection Process For Structural Officials (Echelon II) In Sleman Regency - Muhammad Eko Atmojo; Helen Dian Fridayani (Universitas Muhammadiyah Yogyakarta, 2019)
The administration of government is certainly very influenced by bureaucracy which is an instrument or an organization that helps in realizing or implementing a policy that has been previously set. The open selection is the process of filling in a position by opening a selection to all those who have the competency or ability determined to fill a certain position. This study is aims to analyze the open selection for echelon II Officials both in Yogyakarta Province which is Sleman Regency. The method that used in this study is a qualitative approach which did the depth interview with several stakeholders that involved. The result of this study are the selection mechanism conducted in Sleman Regency in 2017 lasts 2 times and all of them have referred to the applicable regulations and most importantly have implemented a merit system. In the selection implementation the position was carried out by a selection committee formed based on recommendations from KASN (Commission Of The State Civil Apparatus). The involvement of political officials in this case the regent in the open selection process only exists after the selection committee has issued 3 names that have passed. However, the involvement of political officials is positive because it considers the results of the selection. This is also because the Regent will cooperate with one of the 3 names to realize the vision and mission that has been set.Keyword: Open selection, Echelon II, Promotion.